M Stadt : Europäische Stadtlandschaften. - De Michelis, Marco; Bucher, Katrin; Pakesch, Peter; Kunsthaus, Graz (Köln : Walther König, 2006)
Baumann, Thomas ; Bucher, Katrin ; Burden, Chris ; Feldmann, Hans-Peter ; De Michelis, Marco ; Fujihata, Masaki ; Fleury, Sylvie ; Graham, Dan ; Garaicoa, Carlos ; et al.
Kunsthaus Graz am Landesmuseum Joanneum, Graz, Oct 1, 2005 - Jan 8, 2006
kunstcatalogus